From Startup to Scaleup: Growth Concept and Scaleup Issues - Hirokazu ANAI (AAOS Transactions)
In recent years, policy emphasis has shifted from supporting start-ups and entrepreneurs in the early stages of entrepreneurship to fostering a new category of firms: high growth firms (HGFs) or scaleups firms that successfully develop innovative products and aim to expand their scale. The reason is that it has become clear that these firms can have a significant impact on new job creation and economic growth through improved production efficiency and innovation. In the past few years, these companies have been growing faster and bigger, creating unicorns and decacorns. Policy makers around the world compete to create the most unicorns, and some countries have even incorporated them into their policy goals. However, despite these changes in the environment, definitions and conceptualization of HGFs and scaleups have not been fully developed. The questions of what factors are responsible for the creation of these groups of companies and what are the issues involved in fostering these companies remain unanswered. Therefore, the purpose of this study is to organize the scaleups concept, definition and to identify issues in fostering scaleups.